Methodological bases for monitoring technological transformation of regional industry - M. A. Miller (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to the development of methodological tools for tracking the parameters of technological transformation in the production sector of the regional economy. The definition of the concept of monitoring the technological transformation of industry is given, the means, methods, information base and observed parameters of the monitoring process are identified and described. The types of tools for monitoring the technological transformation of industrial enterprises in the region are highlighted. In the article, as part of the justification for monitoring the technological transformation of industry, its purpose, object, subjects, as well as consumers of monitoring results are defined, which include the relevant executive authorities of the subject of the Russian Federation, scientific organizations specializing in conducting scientific research in the field of regional industrial development, and regional industrial enterprises. The general scheme of monitoring of technological transformation in industry is given. Two tools for monitoring the technological transformation of the Omsk Region industry are proposed — the information and analytical system and the expert platform. The tools are based on automating the processing of information about the components of technological transformation using web tools, as well as attracting experts to monitor the transformation processes in the production base of industrial enterprises and analyze unstructured material. The typical difficulties of using tools for monitoring the technological transformation of regional industry are summarized. The results of the analysis of the technological transformation of the regional industry determined by the use of monitoring serve as the basis for the implementation by consumers of the results of monitoring regulatory measures to improve the regulatory and organizational and managerial conditions for the participation of industrial enterprises of the Omsk region in the processes of technological transformation of the production base.